Mr. Johnson [videorecording (DVD)] - Collinson, William, 1984-; Di Castri, Amedeo; Slabolepszy, Paul, 1948-; Cilliers, Jana; Boyd, Clayton (Dreamscape Media, 2023)
After awakening from an almost 50-year coma, 76-year-old David Johnson struggles to adjust until he decides to track down his college sweetheart.